Connecting Peace and Pedagogy in Pakistan - Natasha Khan (NUST Journal of International Peace and Stability, 2022)
Peace education has been propelled to the forefront of pedagogical and conflict transformation praxes. These praxes are necessitated by the growing number of complex conflicts around the world that demand more sophisticated solutions. The National curricula of Pakistan have become an ever more important tool to meet national and international commitments under this approach of conflict transformation. Yet the central challenge(s) that remain for peace education is more than merely teaching about peace and conflict. While engaging with existing values, attitudes, and beliefs, peace education needs to extricate itself from the utopian juxtaposition of peace and conflict as dialectical opposites. It must avoid universal definitions which signal exclusion and either/or solutions and work on constantly recalibrating its own subject matter if it is to enact meaningful social change. It must equally be aware of its tendencies to exclusiveness in practice; pedagogy must not be a one-sided transfer of knowledge, but a system of feedback and communication between learners and educators. Consequently, national policies following the paradigms of education for peace and sustainable development will face the same challenges.